Growth performance and nutritional quality enrichment of Phronima pacifica by Chlorella vulgaris and Chaetoceros calcitrans as natural feed - Vivi Endar Herawati; Zumalallail Nailulmuna; Nurmanita Rismaningsih; Johannes Hutabarat; Pinandoyo Pinandoyo; Tita Elfitasari; PUTUT HAR RIYADI; Ocky Karna Radjasa (Society for Indonesian Biodiversity, 2020)
Abstract. Herawati VE, Nailulmuna Z, Rismaningsih N, Hutabarat J, Pinandoyo, Elfitasari T, Riyadi PH, Radjasa OK. 2020. Growth performance and nutritional quality enrichment of Phronima pacifica by Chlorella vulgaris and Chaetoceros calcitrans as natural feed. Biodiversitas 21: 4253-4259. Phronima pacifica as a natural feed has the potential to replace Artemia sp. because of its high nutritional content. The purpose of this study was to determine the effects of different types of feed for P. pacifica during its culture on its population density, growth rate, and nutritional content because of its potential use as a natural feed for fish. The test animals in this study consisted of P. pacifica at a stocking density of 3 ind/L, which were cultured for 18 d. Then, Chlorella vulgaris and Chaetoceros calcitrans were introduced as enrichment feed for P. pacifica. This study used a completely randomized design with three treatments and three replications. The treatments were as follows: A (100% Chlorella vulgaris), B (100% Chaetoceros calcitrans), and C (50% Chlorella vulgaris and 50% Chaetoceros calcitrans). The results showed that treatment increased the population density of P. pacifica by up to 54.67 ± 0.0038 ind/L by the 12th day. Based on the results of proximate analysis for amino acid and fatty acid profiles, the highest values for proteins and fats were in P. pacifica enriched with Chlorella vulgaris (A) and consisted of 45.45% protein, 7.57% fat, 5.95% eicosapentaenoic acid, and 39.23% lysine. Based on an ANOVA, feeding of P. pacifica with Chlorella vulgaris and Chaetoceros calcitrans had a significant effect on population density, relative growth rate, biomass production, and nutrient value of proteins and fats of P. pacifica (P < 0.05). The best results, including population density, growth rate, weight of biomass, and nutrient content of P. pacifica, occurred after feeding with Chlorella vulgaris.